PROSPECTS FOR THE EXPANSION OF THE WORLD MARKER FOR DESICCATED COCONUT - G.A. HONE; A.D. JOHNSON; A.D. MARTER; W.H. TIMMINS (International Coconut Community, 1992)
The world market for desiccated coconut (DC) is examined within a supply and demand framework. Production and marketing arrangements within DC producing countries are analysed, in addition to consumption trends in the major DC markets of Europe and North America. The prospects for expanding the DC market are then considered, and some potential is found in amas such as: research and development, product promotion and‑markethig strategy.